ANALISIS PREFERENSI PEKERJAAN REMAJA GEN Z ERA DIGITAL DAN ARTIFICIAL INTELLIGENCE DI PROVINSI LAMPUNG - Agus Wibowo; Mudaim; Idyana Adha (Counseling Milenial (CM), 2026)
The development of digital technology has significantly influenced the career preferences of Generation Z adolescents, particularly in determining future occupations and career fields. This study aimed to analyze the career preferences of Generation Z adolescents in Lampung Province in the digital era. The research employed a quantitative approach with a descriptive design. The population consisted of twelfth-grade students from senior high schools and vocational high schools in Lampung Province, with a sample of 500 students selected through simple random sampling. The research instrument used was the Generation Z Adolescent Career Preference Scale, which had been tested for validity and reliability. The validity test results showed that 34 items were valid with validity coefficients ranging from 0.321 to 0.784, while the reliability test obtained a Cronbach’s Alpha coefficient of 0.912, indicating a very high level of reliability. Data analysis techniques used descriptive statistics in the form of percentages and frequency distributions. The findings revealed that the most preferred occupations among Generation Z adolescents were entrepreneur (17.4%), teacher (14.4%), and employee (10.4%). In terms of occupational fields, entrepreneurship had the highest percentage (34.61%), followed by health (17.64%), education (16.29%), and civil servant/military/police sectors (15.84%). The results indicate that Generation Z adolescents tend to prefer careers that are flexible, creative, independent, and aligned with their passions as well as digital technology developments. This study implies the importance of implementing digital-based career guidance and counseling services in schools to assist students in understanding their potentials, recognizing modern work environments, and planning realistic careers in the digital era.